Earthquake Fingerprint of an Incipient Subduction of a Bathymetric High. Issue 14 (22nd July 2022) - Passarelli, Luigi; Cesca, Simone; Nooshiri, Nima; Jónsson, Sigurjón
Abstract: The resistance of bathymetric highs to subduction results in large‐scale morphological distortions of the outer‐rise, trench, and fore‐arc regions. Once subducted, bathymetric highs induce frictional segmentation along the plate interface that may result in increase or decrease of the plate coupling. However, the mechanics of the collision is inferred mostly from geophysical and geological surveys since earthquakes rarely illuminate finer details of the subduction of seafloor relief. A year‐long and energetic seismic sequence at the Loyalty Ridge (LR)‐Vanuatu Trench allowed us to characterize how strain is released along the collision zone. Earthquakes revealed complex fracturing in the outer‐rise and fore‐arc regions and segmentation of the interface with both limited magnitude events and aftershock productivity. The complex earthquake activity associated to the collision and subduction of the LR appears to support a frictionally segmented interface where M w ≥ 8 megathrust earthquakes are unlikely to nucleate. Plain Language Summary: Subduction zones are regions under the sea where two tectonic plates collide and one plate plunges underneath the other. There, the seafloor of the plunging plate slides and rubs under the overlying plate producing high earthquake activity and large earthquakes called megathrust earthquakes. The seafloor is not everywhere flat, but has kilometer long seamounts in some places that form bathymetric highs. When close to subduction, bathymetric highs resist the plunging motion and plow through the overlaying plate. This is a catastrophic process that changes both shape of the subduction and associated seismicity. However, it is not well understood whether subducted bathymetric highs can produce large megathrust earthquakes or not. We studied the earthquake activity along the Loyalty Ridge (LR) (Pacific Ocean) where it collides and slides underneath the Vanuatu subduction zone. The analysis of the seismicity along the LR indicates that the earthquakes are caused by the resistance and bending of the ridge due to the subduction motion. At the plates' contact, less earthquakes occur than expected and they are not as large as in the neighboring subduction segments. In this area, with increased damage induced by the plunging ridge, larger megathrust earthquakes (above M w 8) are unlikely to occur. Key Points: An unusually energetic earthquake sequence provides information about the subduction dynamics of the Loyalty Ridge at the Vanuatu Trench Spatio‐temporal patterns of normal faulting earthquakes along the ridge indicate large‐scale fracturing in resistance to its subduction Ridge subduction leads to a frictionally segmented interface where M w 8+ earthquakes are unlikely to occur